Medan City Tourism Geographical Information System Using Dijkstra Algorithm Method - Zufria, Ilka; Harahap, Aninda Muliani; Rkt, M Ferdiansah (AI Society & STMIK Indonesia, 2022)
Medan City Tourism Office in providing tourism location information is currently still using the official website that only displays explanations about tourism and mapping of tourist location points only, the current system is less efficient and makes tourists or the public not know much about the location or route to be passed and search for tourist attractions in the city of Medan. Researchers try to solve the problem by implementing a geographic information system implemented with OSM (Open Street Map). In this study, data collection using qualitative methods and applications was developed using waterfall methods. The results of the analysis will be described using UML (Unified modelling language). The results of this study show that the geographical information system of tourism to find out the location point and the nearest route can provide benefits to tourists and local people to travel in the city of Medan.